Adiantum japonicum, a new species of the Adiantum pedatum complex (Pteridaceae) from Japan - Zhao, Ting; Zuo, Zheng-Yu; Ebihara, Atsushi; Nakato, Narumi; Soejima, Akiko; Li, De-Zhu; Wen, Jun; Lu, Jin-Mei (Phytotaxa, 2021)
The Adiantum pedatum complex is disjunctly distributed in North America and eastern Asia. In this study, we carried out a detailed morphological study based on 137 specimens representing the biogeographic diversity of this complex. The sequences of eight chloroplast markers of 35 samples were analyzed with maximum likelihood and Bayesian inference. The morphological and phylogenetic analyses support the recognition of a new species of the A. pedatum complex from Japan. We propose the new species as A. japonicum based on the examinations of specimens from Japan and the comparative analyses of the whole complex. This new species can be distinguished from A. pedatum by the erect rhizome and shows significant molecular differences from other species in this complex. A taxonomic description with detailed morphological characters of the new species is presented.